Codex alimentarius : (FAO, 2004)
The joint FAO/WHO Codex Alimentarius Commission is the UN body responsible for establishing international food standards aimed at protecting the health of consumers and ensuring fair practices in the food trade. This publication contains the overarching principles on the risk analysis of foods derived from modern biotechnology and guidelines for food safety assessment of foods derived from recombinant-DNA plants or produced using recombinant-DNA micro-organisms, as adopted by the Commission at its 26th session, held in 2003.